2023
DOI: 10.1186/s42466-023-00240-0
|View full text |Cite|
|
Sign up to set email alerts
|

Guideline “Transient Global Amnesia (TGA)” of the German Society of Neurology (Deutsche Gesellschaft für Neurologie): S1-guideline

Abstract: Introduction In 2022 the DGN (Deutsche Gesellschaft für Neurologie) published an updated Transient Global Amnesia (TGA) guideline. TGA is characterized by a sudden onset of retrograde and anterograde amnesia for a period of one to a maximum of 24 h (with an average of 6 to 8 h). The incidence is estimated between 3 and 8 per 100,000 population/year. TGA is a disorder that occurs predominantly between 50 and 70 years. Recommendations The diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Instead, the patient presented with a TGA. The amnesia attack fulfilled both Caplan’s and Hodges and Warlow's criteria for TGA [ 4 - 7 ]. The episode was witnessed; it involved anterograde amnesia lasting for only a few hours, without any other focal neurological sign or epileptic feature, in the absence of head trauma or loss of personal identity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the patient presented with a TGA. The amnesia attack fulfilled both Caplan’s and Hodges and Warlow's criteria for TGA [ 4 - 7 ]. The episode was witnessed; it involved anterograde amnesia lasting for only a few hours, without any other focal neurological sign or epileptic feature, in the absence of head trauma or loss of personal identity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is not much information regarding the etiology of TGA, it is known that it is more common between the fifth and seventh decades of life, and is usually associated with a trigger, like extenuating physical activity, cold water immersion, receiving bad news, sexual intercourse, or situations associated high levels of stress [ 1 , 2 , 4 ]. There are several theories that propose vascular phenomena, migraine, or epilepsy in the genesis of TGA but they are yet to be proven [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of TGA can only be made in the absence of head trauma or seizures in the 24 hours previous to the ensuing symptoms [2]. The estimated incidence of TGA is between 3-8/100,000 population per year, and its etiology and risk factors are not entirely known [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations. Following publication of the original article [1], the authors reported that the author name "Nils Nellessen" was incorrectly written as "Nils Nellesen".…”
Section: Publisher's Notementioning
confidence: 99%